ANALYSIS OF DEXAMETHASONE SODIUM PHOSPHATE INJECTION AND OPHTHALMIC SOLUTION BY HPLC, KINETIC INTERPRETATION AND DETERMINATION OF SHELF LIFE (Journal of Sciences, Islamic Republic of Iran)
The use of accelerated temperature stability studies using the Arrhenius relationship is routine for estimating the stability of a drug at room temperature. Therefore, the acceleration method is used to determine the expiration date of dexamethasone aqueous formulation manufactured in Iran. A high-performance liquid chromatography (HPLC) method utilizing ultraviolet (UV) detection for dexamethasone disodium phosphate and ophthalmic solution is described. Using the kinetic information generated from the high-temperature studies, at 60,70, 80 and 90°C, an Arrhenius plot for dexamethasone disodium phosphate degradation was constructed and the shelf-life of the drug was estimated